Avaliação do conhecimento e atitudes do estudante de Medicina a respeito da hanseníase e do seu ensino na Universidade Federal de Minas Gerais - Cynthia Rosetti Portela Alves (2013)
Leprosy is an infectious disease of chronic evolution that affects the skin and peripheral nerves. If not treated properly and early, it can develop into physical disabilities and deformities, those responsible in large part by social stigma and marginalization. Although curable, still represents a major public health problem, Brazil is the second most endemic country in the world, second only to India. However, ignorance of various aspects of this disease is great, being surrounded by myths and misconceptions, even among health professionals. Information, education and communication are key measures for its prevention, helping in the fight against fear and prejudice. Better understand leprosy during the formative process of the health professional may help to improve knowledge about the disease, allowing early detection, improved patient care and prevention of its complications and sequelae. For these reasons it is expected that the newly graduated physician is aware of its epidemiological relevance, be prepared to recognize its signs and symptoms and enabled to clarify basic questions of the community. This study aimed to assess the knowledge and attitudes of medical students about leprosy and its teaching at the Federal University of Minas Gerais (UFMG). The research project was developed in the Graduate Professional Master of Health Promotion and Prevention of Violence at the Faculty of Medicine. The work is structured in the form of two articles. Article 1, "Teaching hansenology: current challenges" - is a review article that presents the strategies and related hansenology teaching experience in health undergraduate courses and the professionals who work in patient care, in view to reflect the challenges for teaching with new settings of endemic and discuss proposed alternative approach. Article 2 "hansenology teaching evaluation by students of a Brazilian public medical school" - is an article of results that aimed to evaluate the teaching of leprology in significant medical public school, located in the southeastern Brazilian metropolis that has low rates of prevalence of leprosy. The training of human resources is a basic action approach of leprosy, since its control is based on early diagnosis and appropriate treatment. The small number of cases observed in Basic Health Units in the areas of low prevalence, turned its teaching into a challenge. In the analysis by means of a transverse comparative study between two parallel groups of students (incoming and internal) of the medical course, it was observed that most joined knowledge already showing signs and symptoms of the     disease. Greater theoretical knowledge was evidenced by internal as well as more favorable attitudes about the disease, when compared to freshmen. But this gain has not reached everyone, as expected for a disease treated as a public health problem in the country. Most internal leprosy reported that the topic was addressed in the course, however practical teaching proved insufficient. Students had the opportunity of practical experience with patients were more confident in their ability to meet similar cases. The practical scenario that allowed the student to meet leprosy patients was predominantly in the Dermatology connected to a reference center. Teaching hansenology in undergraduate courses in medicine should be rethought and adapted to the local epidemiological reality.